2015
DOI: 10.3171/2014.10.spine1474
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution direct microstimulation mapping of spinal cord motor pathways during resection of an intramedullary tumor

Abstract: Despite the use of advanced microsurgical techniques, resection of intramedullary tumors may result in significant postoperative deficits because of the vicinity or invasion of important functional tracts. Intraoperative monitoring of somatosensory evoked potentials and transcranial electrical motor evoked potentials has been used previously to limit such complications. Electromyography offers an opportunity for the surgeon to map the eloquent tissue associated with the tumor using intraoperative motor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 7 publications
(6 reference statements)
0
10
0
2
Order By: Relevance
“…A few reports in the literature focus on techniques useful for real-time identification of the anatomical site of the CST within the SC. 10,12,13,17,38 Duffau et al, 13 in 1998, described the use of a modified bipolar probe (4 mm distance of stimulating surfaces) for direct medullary electrical stimulations (60 Hz, biphasic square-wave pulses with 1 msec/phase, 0.9 mA) during surgery in 3 patients with IMSCT. These authors concluded that direct medullary electrical stimulation is a safe, easy, precise, and reliable method of reducing morbidity during SC surgery.…”
Section: Intramedullary Motor Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…A few reports in the literature focus on techniques useful for real-time identification of the anatomical site of the CST within the SC. 10,12,13,17,38 Duffau et al, 13 in 1998, described the use of a modified bipolar probe (4 mm distance of stimulating surfaces) for direct medullary electrical stimulations (60 Hz, biphasic square-wave pulses with 1 msec/phase, 0.9 mA) during surgery in 3 patients with IMSCT. These authors concluded that direct medullary electrical stimulation is a safe, easy, precise, and reliable method of reducing morbidity during SC surgery.…”
Section: Intramedullary Motor Mappingmentioning
confidence: 99%
“…These authors concluded that mapping SC motor tracts with direct SC stimulation and electromyographic recording facilitated a more extensive resection. In 2015, Gandhi et al 17 described the use of intraoperative motor fiber tract stimulation to map the CST associated with a cervicomedullary junction cystic ependymoma. High-resolution motor mapping was performed using a Kartush concentric bipolar stimulating probe (overall width of 2 mm) with a biphasic waveform (repetition rate 60.11 Hz, pulse width 1.0 msec, stimulation intensities ranging from 0.1 to 1.0 mA) with registrations on individual muscle groups.…”
Section: Intramedullary Motor Mappingmentioning
confidence: 99%
“…We elaborated on an important aspect that has not received sufficient attention so far 14. In a previous publication we demonstrated that muscle responses can be elicited not only by stimulation of the CT but also by stimulation of the DC 18.…”
Section: Discussionmentioning
confidence: 99%
“…This technique may have some advantage compared with MEP, which generally informs after occurrence of an injury because direct microstimulation allows the identification of the motor pathways before continuing of resection and in this way helps to avoid their injury. When used in conjunction with MEP, direct microstimulation makes the operation more safe and preservation of the pyramidal tracts more possible, informing when to stop resection to prevent neurological morbidity …”
Section: Discussionmentioning
confidence: 99%